2012
DOI: 10.1016/j.bandl.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement learning in young adults with developmental language impairment

Abstract: The aim of the study was to examine reinforcement learning (RL) in young adults with developmental language impairment (DLI) within the context of a neurocomputational model of the basal ganglia-dopamine system (Frank et al., 2004). Two groups of young adults, one with DLI and the other without, were recruited. A probabilistic selection task was used to assess how participants implicitly extracted reinforcement history from the environment based on probabilistic positive/negative feedback. The findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 97 publications
6
33
1
Order By: Relevance
“…Other studies of adults with DLI have also found that adults with DLI score lower on tests of PIQ (Fidler et al, 2011;Lee & Tomblin, 2012;Rost & McGregor, 2012) and have lower educational attainment (Conti-Ramsden & Durkin, 2012). This suggests that our group with DLI was representative of the population of adults with DLI; however, the group with typical language had several members with higher than typical PIQ.…”
Section: Limitationscontrasting
confidence: 42%
See 3 more Smart Citations
“…Other studies of adults with DLI have also found that adults with DLI score lower on tests of PIQ (Fidler et al, 2011;Lee & Tomblin, 2012;Rost & McGregor, 2012) and have lower educational attainment (Conti-Ramsden & Durkin, 2012). This suggests that our group with DLI was representative of the population of adults with DLI; however, the group with typical language had several members with higher than typical PIQ.…”
Section: Limitationscontrasting
confidence: 42%
“…The group with DLI differed from the group with typical language in both language ability and PIQ. This has frequently been the case in studies of adults with DLI (Fidler et al, 2011;Lee & Tomblin, 2012;Rost & McGregor, 2012;Tomblin et al, 1992). Because somewhat lower PIQ is characteristic of adults with DLI, matching on PIQ risks creating groups that are not representative of the population.…”
Section: Group Differences In Piqmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, with regard to the posited role of the basal ganglia in language acquisition and use, an impairment of RL in general appears to accompany developmental language impairment (Lee & Tomblin, 2012). 18 Likewise, with regard to the posited involvement of the hippocampus in language acquisition (Edelman, 2011), individual differences in hippocampal neuroanatomy in infancy predict language performance a few months later (Can, Richards, & Kuhl, 2013).…”
Section: Discussionmentioning
confidence: 99%